Thrombotic microangiopathies: First report of 294 cases from a single institution experience in Argentina - Dos Santos, Célia (2020)
Introduction: Thrombotic microangiopathies (TMAs) are rare disorders associated with fatal outcomes if left uncared for. However, healthcare problems in developing countries tend to limit medical assistance to patients. Methods: We prospectively studied an Argentine cohort of 294 consecutive patients from 2013 to 2016. Patients’ subcategory classification relied on clinical symptoms and presence or absence of trigger events associated with TMA. Results: Main suspected disorders were the primary TMAs known as thrombotic thrombocytopenic purpura (TTP) (n = 72/294, 24%) and atypical haemolytic uraemic syndrome (aHUS) (n = 94/294, 32%). In acute phase, demographic parameters for acquired TTP (aTTP) (n = 28) and aHUS (n = 47) showed that both groups were characterised by a young median age (37 and 25 years, respectively) and female predominance (60% and 86%). Median of a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13 activity was significantly lower in aTTP than in aHUS group (1.4% vs 83%) and was associated with a more severe thrombocytopenia (15 × 109 vs 53 × 109/L). Creatinine (Cr) and urea (Ur) were significantly increased in aHUS compared to aTTP subjects (Cr: 3.7 vs 0.7 mg/dL, Ur: 118 vs 33 mg/dL). Gastrointestinal and neurological symptoms were more frequent in aHUS and aTTP, respectively. Conclusion: The first description of a TMA cohort in Argentina revealed similar clinical presentations to those of other countries.